1989
DOI: 10.1021/jf00088a031
|View full text |Cite
|
Sign up to set email alerts
|

Urea analysis for wines

Abstract: An analysis for urea in wine was developed in which urea is isolated by ion exchange and then derivatized with 1-phenyl-1,2-propanedione 2-oxime. Measurements of the derivative are made by colorimetry. The analysis gave good linear response to additions of 0-50 mg/L of urea to either red or white wine. Blank experiments in which either urea or l-phenyl-l,2-propanedione 2-oxime was withheld with either red or white wine samples or model solutions gave less than 1.0 mg/L of urea in all cases. Good agreement was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Recent methods in the literature for determination of urea in wines are based on enzymic analysis and monitoring of the pH change using two capillary glass electrodes capable of quantifying changes of pH of 0.001 units produced in the hydrolysis by urease [6]; on HPLC with a previous derivatisation reaction for facilitating separation [7,8] or on derivatisation with 1-phenyl-propan-1,2-dione 2-oxime in ethanol and photometric monitoring at 540 nm [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent methods in the literature for determination of urea in wines are based on enzymic analysis and monitoring of the pH change using two capillary glass electrodes capable of quantifying changes of pH of 0.001 units produced in the hydrolysis by urease [6]; on HPLC with a previous derivatisation reaction for facilitating separation [7,8] or on derivatisation with 1-phenyl-propan-1,2-dione 2-oxime in ethanol and photometric monitoring at 540 nm [9].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the Method for the Determination of Urea in Sugar Cane Distilled Spirits. During optimization of the method described by Almy and Ough (5), some modifications (A-C) were undertaken in the preparation of the acid solution and also in the temperature and time necessary for the formation of the derivative. Analysis of the recoveries of urea using the different procedures at three spiking levels is indicated in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, urea is also formed as a consequence of yeast metabolism . Studies have indicated that arginine and citrulline are the main precursors , and that the yeast strain and fermentation temperatures can also cause increased urea accumulation in wines .…”
Section: Introductionmentioning
confidence: 99%
“…We embarked on developing a simple and convenient nonradiolabel method to quantify urea accumulated in the stratum corneum. In this method (the "tape stripping-colorimetry (T-C) method"), the urea transferred to and retained in the stratum corneum is retrieved by tape stripping and is then measured by colorimetry (urease-glutamate dehydrogenase (GLDH)), [17][18][19][20][21][22] a measurement technique commonly used in blood tests. We here investigated the amount of formulation that must be applied for accurate measurement of the accumulated urea using the T-C method, used these conditions to show the relationship between the concentration of urea in the formulation (10 or 20%) and the quantity of urea accumulated in the stratum corneum, and assessed the effectiveness of the T-C method as a means of evaluating formulations.…”
mentioning
confidence: 99%